Teknologi Tepat Guna Akuaponik Pada Lahan Sempit oleh Kelompok 02 KKN-T UPN Veteran Jawa Timur di Desa Banjaragung, Bareng - Indira Reva Labibah; Faiza Aulia Novadinastia; Marsha Amanda Fahrasyahda; Assyfaul Baity Zuraj; Putri Abidah Fauziyyah; Erin Dwi Cahyani; Ni Putu Kania Devya; Mu’tasim Billah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Along with the development of regions in Indonesia, followed by population growth, there will be an increase in development and settlements that affect the environment to become quite dense. This resulted in limited land and water so that cultivation activities were also limited. Banjaragung Village is a village located in Bareng District, Jombang Regency. The majority of the livelihoods of the residents of Banjaragung Village are farmers. The aquaponics technique is suitable for application in Banjaragung Village because it includes simple agricultural technology in the form of cultivating fish and plants in one bucket (Budikdamber). The aim of implementing the aquaponics program is to take advantage of narrow land by making minders so that the harvest is expected to generate creative economic opportunities in society. There are two implementation methods, namely the holding of the Budikdamber Appropriate Technology socialization which was attended by PKK mothers and the BPP (Agricultural Extension Agency) Bareng and direct demonstrations. The results obtained are an increase in public knowledge about Budikdamber, can meet family food needs, and improve the community's economy.